Membrane Processes. (1st October 2018) - Pellegrin, Marie‐Laure; Aguinaldo, Jorge; Arabi, Sara; Sadler, Mary E.; Greiner, Anthony D.; Wong, Joseph; Dow, Andrew; Burbano, Marie S.; Danker, Bryce; Diamond, Jason
Abstract : This review, for literature published in 2017, contains information related to membrane processes for municipal and industrial applications. This review is a subsection of the Treatment Systems section of the annual Water Environment Federation literature review and covers the following topics: membrane bioreactor (MBR) configuration, design, nutrient removal, operation, industrial treatment, anaerobic membrane systems, reuse, microconstituents removal, membrane technology advances, membrane fouling, and modeling. Other sub‐sections of the Treatment Systems section that might relate to this literature review include: Biological Fixed‐Film Systems, Activated Sludge and Other Aerobic Suspended Culture Processes, Anaerobic Processes, and Water Reclamation and Reuse. The following sections might also have related information on membrane processes: Industrial Wastes, Hazardous Wastes, and Fate and Effects of Pollutants.